Dynamics of structural changes in the somatosensory cortex in rats with various neurocognitive disorders after traumatic brain injury - Mizyakina , K.V.; Dzyak , L.A.; Tverdokhlib , I.V. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. Information about the sensitivity of different neurons and neuroglia cells to injury and their ability to recover depending on the location of the damage and the nature of microcirculation changes in the post-traumatic period require significant clarification. The study aims to study the tissue and cellular posttraumatic changes in the structure of the somatosensory cortex of rats with various neurocognitive disorders at different times after severe traumatic brain injury. Methods. A "shock acceleration model" was used to reproduce severe traumatic brain injury in rats. According to the results of neurological tests, the rats were divided into three groups: 1) the first – animals after trauma with neurocognitive disorders and memory disorders; 1) the second – animals after trauma with neurocognitive disorders without memory disorders; 3) comparison group – animals after trauma without neurocognitive disorders. A histological, morphometric and immunohistochemical study of the somatosensory cortex was carried out using the markers β-tubulin, Synaptophysin, GAP43, NCAM1, N-cadherin, GFAP. Results. In animals with neurocognitive disorders, a moderate decrease in the total content of neurons of different types in the somatosensory cortex is observed, while in animals without cognitive deficits, the density of neurocytes does not differ from the normal level. The suppressed expression of Synaptophysin in the somatosensory cortex in rats with neurocognitive disorders does not change significantly 20 and 40 days after injury and remains at a low level. In animals of the comparison group, the density of p38-positive synapses is restored during the post-traumatic period. 10 days after injury, in animals of all groups, a moderate accumulation of CD56- and N-cadherin-positive protoplasmic astrocytes in the pericapillary spaces is observed, which is often associated with foci of edema and increased mitotic activity of gliocytes. In animals with neurocognitive disorders, in some cases, astroglia form cell layers on the surface of microvessels in the form of dense couplings, which indicates the blockage of transendothelial transport. 40 days after injury, the number of damaged microvessels with layers of astrocytes on the outer surface is significantly reduced. Conclusion. 10 days after injury, moderately pronounced neurodegenerative and destructive changes occur in the somatosensory cortex due to the post-traumatic cytotoxic cascade. 20 and 40 days after injury, signs of neuroinflammation are reduced regardless of the degree of cognitive deficit.